Про інституційні засади регламентації фінансово-господарської діяльності - Андрушків, Б.М; Кирич, Н.Б.; Стойко, І.І.; Погайдак, О.Б.; Мельник, Л.М. (Культура народов Причерноморья, 2013)
У статті обґрунтовано необхідність розробки і впровадження законодавчо-
регламентуючого засобу фінансово-економічної і господарської діяльності. Дано пропозиції з
формування інституційних засад Економічної Конституції України. В статье обоснована необходимость разработки и внедрения нормативно-
регламентирующего средства финансово-экономической и хозяйственной деятельности. Даны
предложения по формированию институциональных основ Экономической Конституции Украины. The need for the development and implementation of regulations governing financial and economic
activity of economic systems is substantiated in the article.
The problems of permanent economic reformations in the conditions of unstable political and economic relations
are considered in the article. Under these circumstances, the key attention is paid to the need for scientific
ground, development and implementation of a legal, regulatory, financial and economic lever of sustainable
functioning of economic systems and public bodies.
Currently, there is no reliable and effective mechanism for interaction between the economy, the people and the
government, the society's impact on the government; there is no reliable method of social control over the
activities of the elected representatives and officials; but there is an urgent need for a comprehensive national
system of Ukrainian democracy and its influence on economic processes.
The article describes the proposed organizational, economic, legislative, legal, spiritual, and cultural resources
to build a reliable economic system, with the "Economic Constitution (law) of Ukraine" (ECU) as an imperative,
on the basis of which the ECU institutional framework must be formed across the state, they should contribute to
the economy solution to the crisis condition. For this purpose, it is necessary to determine the economic
guidelines and to develop appropriate national programs.
Based on the analysis made, the implementation mechanism of three–component paradigm of the ECU
fundamental institutional foundations and their stages is proposed.